Pelaksanaan Pendaftaran Peralihan Hak Atas Tanah Bekas Milik Adat - Siregar, Wulandari; Adhim, Nur (Program Studi Magister Kenotariatan, Fakultas Hukum, Universitas Diponegoro, 2024)
ABSTRACTFormer customary community land can be transferred through sale, purchase, gift, or inheritance, with a mandatory registration process to be completed beforehand. The registration of these land transfers is vital to prevent disputes among the parties involved. This study aims to explore the mechanisms for registering the transfer of rights over former customary land and identify the challenges faced in this process. Employing a normative juridical method, the research examines Indonesian laws and regulations related to the registration of former customary land. The findings indicate that the registration process involves confirming the conversion of land status, which provides legal certainty and protection for landowners, other interested parties, and the government. This procedure is essential for realizing orderly land administration and avoiding potential conflicts.Keywords: Land; Transition; Registration. ABSTRAKTanah bekas masyarakat adat dapat dialihan melalui jual beli, hibah, atau waris dengan wajib melakukan pendaftaran terlebih dahulu. Pendaftaran peralihan hak atas tanah bekas milik adat wajib dilakukan untuk menghindari perselisihan para pihak yang bersangkutan. Dalam penelitian ini bertujuan untuk mengetahui mekanisme pendaftaran peralihan hak atas tanah bekas adat dan penyelesaian terhadap hambatan tersebut. Metode penelitian yang digunakan adalah yuridis normatif dengan mengkaji peraturan perundang-undangan pendaftaran peralihan tanah bekas adat di Indonesia. Hasil penelitian menunjukkan bahwa pendaftaran tanah bekas milik adat dilakukan melalui penegasan konversi, memberikan kepastian hukum dan perlindungan kepada pemilik hak atas tanah, pemangku kepentingan lainnya, dan pemerintah demi terwujudnya tertib administrasi pertanahan.Kata Kunci: Tanah Adat; Peralihan; Registrasi.